Elective neck dissection in patients with radio‐recurrent and radio‐residual squamous cell carcinoma of the larynx undergoing salvage total laryngectomy: Systematic review and meta‐analysis. Issue 11 (10th August 2019) - Lin, Daniel J.; Lam, Alyson; Warner, Laura; Paleri, Vinidh
Abstract: Background: Approximately 30% of nonsurgically treated patients with laryngeal squamous cell carcinoma will suffer recurrence, and many will be clinically N0; the indication for elective neck dissection (END) remains uncertain. We aimed to determine whether END is indicated during salvage laryngectomy. Methods: Systematic review and meta‐analysis. Results: A total of 1141 patients were identified from 17 studies. Occult nodal positivity was 13.7% (106/775) confidence interval (CI) 11.3%‐16.1%; higher in supraglottic than glottic disease (17.8%, CI 10.3%‐25.3% vs 12%, CI 7.1%‐16.9%, P = .18). No significant difference existed between END vs observation in 5‐year disease free survival (odds ratio [OR] = 0.76, CI = 0.49‐1.17, P = .21, I 2 = 10%) and overall survival (OS; OR = 0.96, CI = 0.65‐1.41, P = .82, I 2 = 54%). Conclusions: No significant survival advantage was found for END vs observation. Individual studies trended towards improved survival with END in supraglottic and locally advanced tumors. These factors should be considered when deciding on END in salvage laryngectomy.